Difficulties of breastfeeding in children with Down Syndrome (Research, Society and Development, 2020)
Objective: To present scientific evidence based on a systematic literature review (PRISMA) on the possible difficulties of breastfeeding in children with Down Syndrome (DS). Methodology: The search for articles was carried out in the databases Scielo, Lilacs, Pubmed, Scopus, Bireme and Web Of Science, there was no restriction on location, period and language. For the selection of studies, the combination based on the Medical Subject Heading Terms (MeSH) was used. Four studies that scored ≥ 6 points according to the qualitative score protocol proposed by Pithon et al. (2015). Results: Studies show that the vast majority of mothers of babies with DS have knowledge about the benefit of exclusive breastfeeding for newborns with this type of syndrome, however some factors prevent breastfeeding, the most cited being hospitalization in neonatal unit, frustration or depression, perceived insufficiency of milk and difficulty in sucking, in addition to the lack of instruction by some health professionals. Conclusion: Children with DS are breastfed less frequently compared to children without disorders or syndromes. Therefore, active support, education and collaboration between health team members and mothers of babies with DS are essential for successful breastfeeding, revealing that health professionals have an important role in the success or failure of exclusive breastfeeding.